Pelatihan Penulisan Judul Dan Introduction Dalam Karya Ilmiah Bagi Mahasiswa - Siti Pratiwi Husain (Mopolayio : Jurnal Pengabdian Ekonomi, 2021)
The problem in this research is students still do not understand when writing scientific papers, in choosing a topic or problem, determining the title of a scientific paper, making an introduction, as well as references or data needed in writing scientific papers. The purpose of this service activity is to increase the knowledge of the participants about the importance of writing scientific papers and to improve the ability of the participants to determine the title and make an introduction properly and correctly according to the guidelines for writing scientific papers. The method used is the method of lectures, discussions and exercises. The results of the service activities show that 85% of participants who come from students who take part in this training activity can determine the title of the scientific work and prepare an introduction in the scientific work.